Aging-induced enhancement of corrosion resistance in Al-4Ni-1Mn alloys through Al3(Sc, Zr) precipitates - Anuchit Masthong; Dmitry Eskin; Chaowalit Limmaneevichitr; Phromphong Pandee; Onnjira Diewwanit; Suwaree Chankitmunkong (Journal of Alloys and Compounds, 2025)
Al-Ni-Mn alloys are attractive for high-temperature, corrosive environment due to the formation of stable intermetallic compounds that can reduce corrosion susceptibility. This study showed that the additions of Mn, Sc , and Zr in Al-4 % Ni alloys significantly enhanced hardness and thermal stability through the simultaneous effect of transformation of the Al + Al 3 Ni to Al + Al 9 (Ni, Mn) 2 eutectic and precipitation of Al 3 (Sc, Zr). The thermal stability of an Al-4 % Ni-1 % Mn alloy was very good when exposed to 350 °C for 60 h. Additionally, the hardness substantially increased in an Al-4 % Ni-1 % Mn alloy with the addition of Sc and Zr, showing an approximate increase of 30 %. The highest hardness achieved was approximately 50 % higher with the optimal Sc and Zr content as compared to the Al-4Ni-1Mn alloy. Addition of 1 % Mn to an Al-4 % Ni alloy decreased the current density (I corr ) and increased the corrosion potential (E corr ), indicating better corrosion resistance . The effects of Sc and Zr additions on corrosion were also investigated, revealing that the increased Sc and Zr content led to more aggressive corrosion in the as-cast condition due to the eutectic coarsening and a high solid solution concentration of Sc and Zr that led to microstructural instability and electrochemical effects . However, after aging at 350 °C, the corrosion resistance significantly improved due to the Al 3 (Sc, Zr) precipitates that interrupted the corrosion path. • Adding Mn to Al-4Ni alloys increased hardness and improved thermal stability. • As-cast Al4Ni1MnScZr alloys showed reduced corrosion resistance. • Aging the (Sc + Zr)-containing alloys at 350 ºC improved corrosion resistance. • Improved corrosion resistance is due to protective oxide layer. • Improved corrosion resistance is due to precipitates obstructing corrosion path.
Keywords: Aluminum Alloy Microstructure Properties; Aluminum Alloys Composites Properties; Corrosion Behavior and Inhibition